高速插齿机主传动机构的优化设计 - 王德俊; 崔国英; 杨守福 (Jixie chuandong)
A six - bar driving mechanism for the high speed gear shaper is presented. Compared with the traditional crank - slider driving mechanism, this new mechanism is better because of its changeable stroke, smoother velocity and faster return.